Integration Reduction Formula


For Integration Recurrence Formula or reduction formula, it is important to set a relationship between two consecutive terms by using mostly the integration by parts.

Worked Example of Integration Reduction Formula

Question 1

For any integer \(m \ge 0\) let \(\displaystyle I_m = \int_{0}^{1} x^m (x^2 – 1)^5 dx \).
Prove that for \( \displaystyle m\ge 2, I_m = \frac{m-1}{m+11} I_{m-2}.\)

\( \begin{aligned} \require{color} \displaystyle
\frac{d}{dx}(x^2 – 1)^6 &= 6(x^2 – 1)^5 \times 2x \\
\frac{d}{dx} \frac{(x^2 – 1)^6}{12x} &= (x^2 – 1)^5 \\
I_m &= \int_{0}^{1} x^m \times \frac{d}{dx}\frac{(x^2-1)^6}{12x} dx \\
&= \int_{0}^{1} x^{m-1} \times \frac{d}{dx}\frac{(x^2-1)^6}{12} dx \\
\color{red} u = x^{m-1},\ &\color{red}v’=\frac{d}{dx}\frac{(x^2-1)^6}{12} \\
\color{red} u’ = (m-1)x^{m-2},\ &\color{red}v=\frac{(x^2-1)^6}{12} \\
I_m &= \Big[x^{m-1} \times \frac{(x^2-1)^6}{12}\Big]_{0}^{1} – \int_{0}^{1} (m-1)x^{m-2} \times \frac{(x^2 – 1)^6}{12}dx &\color{red} \int uv’ = uv – \int u’v \\
&= 0 – \frac{m-1}{12} \int_{0}^{1} x^{m-2}(x^2-1)^6 dx \\
&= – \frac{m-1}{12} \int_{0}^{1} x^{m-2}(x^2-1)^5(x^2-1) dx \\
&= – \frac{m-1}{12} \int_{0}^{1} \Big[x^{m}(x^2-1)^5 – x^{m-2}(x^2-1)^5 \Big] dx \\
&= – \frac{m-1}{12} \int_{0}^{1} x^{m}(x^2-1)^5 dx + \frac{m-1}{12} \int_{0}^{1} x^{m-2}(x^2-1)^5 dx \\
I_m &= – \frac{m-1}{12} I_{m} + \frac{m-1}{12} I_{m-2} \\
I_m + \frac{m-1}{12} I_{m} &= \frac{m-1}{12} I_{m-2} \\
\frac{m+11}{12} I_{m} &= \frac{m-1}{12} I_{m-2} \\
\therefore I_m &= \frac{m-1}{m+11} I_{m-2} \\
\end{aligned} \\ \)

Question 2

Show that \( \displaystyle nA_n = \frac{2n-1}{2}A_{n-1} \) for \( \displaystyle A_n = \int_{0}^{\frac{\pi}{2}} \cos^{2n}x dx, n \ge 1\).

\( \begin{aligned} \displaystyle \require{color}
A_n &= \int_{0}^{\frac{\pi}{2}} \cos^{2n-1}x \cos x dx \\
&\color{red} u = \cos^{2n-1},\ \color{red}v’=\cos x \\
&\color{red} u’ = (2n-1) \cos^{2n-2}(-\sin x),\ \color{red} v= \sin x \\
&= \Big[\cos^{2n-1} \sin x\Big]_{0}^{\frac{\pi}{2}} – \int_{0}^{\frac{\pi}{2}} (2n-1) \cos^{2n-2} x (- \sin x) \sin x dx \\
&= \int_{0}^{\frac{\pi}{2}} (2n-1) \cos^{2n-2} x \sin^2 x dx \\
&= \int_{0}^{\frac{\pi}{2}} (2n-1) \cos^{2n-2} x (1 – \cos^2 x) dx \\
&= (2n-1) \int_{0}^{\frac{\pi}{2}} \cos^{2(n-1)} x dx – (2n-1) \int_{0}^{\frac{\pi}{2}} \cos^{2n} x dx \\
A_n &= (2n – 1)A_{n-1} – (2n – 1)A_n \\
2n A_n &= (2n – 1)A_{n-1} \\
\therefore A_n &= \frac{2n-1}{2n} A_{n-1} \\
\end{aligned} \\ \)

 

Algebra Algebraic Fractions Arc Binomial Expansion Capacity Chain Rule Common Difference Common Ratio Differentiation Double-Angle Formula Equation Exponent Exponential Function Factorials Factorise Functions Geometric Sequence Geometric Series Index Laws Inequality Integration Kinematics Length Conversion Logarithm Logarithmic Functions Mass Conversion Mathematical Induction Measurement Perfect Square Perimeter Prime Factorisation Probability Proof Pythagoras Theorem Quadratic Quadratic Factorise Rational Functions Sequence Sketching Graphs Surds Time Transformation Trigonometric Functions Trigonometric Properties Volume




Your email address will not be published.